2021
DOI: 10.1177/17246008211065472
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the RASSF1A gene promoter as the tumor DNA marker for nasopharyngeal carcinoma

Abstract: Background RASSF1A is a tumor suppressor gene. The methylation of RASSF1A has been reported to be associated with nasopharyngeal tumorigenesis. However, the heterogeneity was high among different studies. A meta-analysis was performed to evaluate the value of RASSF1A methylation for the diagnosis and early screening of nasopharyngeal carcinoma. Methods Relevant articles were identified by searching the MEDLINE database. Frequency and odds ratio (OR) were applied to estimate the effect of CDH-1 methylation base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…While clinically validating SEPT9 and RASSF1A gene methylation for the diagnosis of nasopharyngeal carcinoma, our study identifies and analyzes for the first time the association between H4C6 gene methylation and NPC with the aim of exploring the potential of gene methylation as a new biomarker for early detection of NPC. Here, targeting new genes we found that H4C6 was frequently methylated in 68.75% of NPC tissues, which is a higher frequency of methylation compared to other genes reported to be hypermethylated in NPC [ 17 ] . H4C6 methylation levels were also significantly higher in the nasopharyngeal cancer group than in the non-nasopharyngeal cancer control group ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…While clinically validating SEPT9 and RASSF1A gene methylation for the diagnosis of nasopharyngeal carcinoma, our study identifies and analyzes for the first time the association between H4C6 gene methylation and NPC with the aim of exploring the potential of gene methylation as a new biomarker for early detection of NPC. Here, targeting new genes we found that H4C6 was frequently methylated in 68.75% of NPC tissues, which is a higher frequency of methylation compared to other genes reported to be hypermethylated in NPC [ 17 ] . H4C6 methylation levels were also significantly higher in the nasopharyngeal cancer group than in the non-nasopharyngeal cancer control group ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Dammann et al, first reported that the loss of expression of RASSF1A in lung cancer was associated with methylation of its CpG-island promoter [ 59 ]. Numerous research studies have demonstrated the abnormal expression of RASSF1A in different kinds of tumors, such as nasopharyngeal carcinoma, breast cancers, and ECs [ 60 , 61 , 62 ]. The overwhelming majority of reports revealed that the CpG island in the RASSF1A promoter was hypermethylated, which has been linked to the malignant transition of early benign tumors into later invasive carcinomas [ 63 , 64 ].…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%